Evaluation of preoperative oral hygiene in patients with maxillofacial fractures: a retrospective clinical study - Silva, Bruno Frota Amora; Lima, Danilo Lopes Ferreira; Lima-Filho, Roberto de Sousa; Barros, Rubens de Paulo Sampaio; Magalhães, Vera Araújo; da Silva, Carla Welch; Borges, Eymard Vieira; Gomes-Junior, George Matos Ferreira; Carvalho, Paulo Henrique Rodrigues; Benevides, Breno Souza; Araújo-Neto , Stélio da Conceição; Menezes-Junior , José Maria Sampaio; et al. (Brazilian Journal of Case Reports, 2021)
The purpose of this study was to know the oral epidemiological profile of patients admitted in a public hospital in the state of Ceará in the immediate preoperative period using the Simplified Oral Hygiene Index (IHO-S). This is a cross-sectional retrospective study of 40 male patients and 4 female patients hospitalized who underwent surgical treatment of maxillofacial fractures. The mean age of the patients was 31.27 years, presenting 21 patients (52.5%) with good oral condition, 18 patients (45%) regular condition and only 1 (2.5%) with poor oral condition. Although oral hygiene has been considered good, studies that emphasize the removal of bacterial biofilms should be performed for patients who have obtained the worst results, in order to reduce the problems that these poor results may cause. Through this study the importance of the dental surgeon in a hospital environment is apparent, acting in the treatment and prevention of factors associated with the oral cavity during the period of hospitalization.